Immigration status and property crime: An application of estimators for underreported outcomes - Georgios Papadopoulos (IZA Journal of Migration, 2014)
This paper studies the individual-level relationship between immigration and property crime in England and Wales using crime self-reports from the Crime and Justice Survey. Models that account for underreporting are used, since this is a major concern in crime self-reports. The results indicate that the reported crime is substantially underreported, but if anything, immigrants are less likely to underreport than natives. More importantly, controlling for underreporting and basic demographics, the estimates across all model specifications, although imprecise, indicate that immigration status and property crime are negatively associated. We finally find that the estimated relationship between immigration status and property crime differs across regions and ethnic groups.
Keywords: K42; J15; J22; C25; C51; 330; Criminal Behaviour; Immigration; Self-reports; Underreporting; NB2-Logit